Family is the Main Pillar of Children Character Education - Parianto, Parianto; Kalsum, Umi (ALACRITY : Journal of Education, 2024)
The family as one of the three educational centers is tasked with forming positive habits (habit formation) as a strong foundation in informal education. This research is a type of library research (Library Research), namely research that examines and explores various written sources related to the theme discussed by the author, namely the concept of family as the main pillar of character education in children as the author's main reference. Based on the description of research data and discussions that have been expressed, the family has an important role in forming a child's character. Education in the family is the initial and main education for a human being. In order to create a generation that has strong character and strong faith and Islam, it is necessary to instill Islamic personality values ??in children. Character education is an integrative and comprehensive education